2023
DOI: 10.3389/fimmu.2023.1139391
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen4+-MDSC in Helicobacter-induced gastric metaplasia reveals role for GTPases

Abstract: IntroductionMDSCs express SCHLAFEN 4 (SLFN4) in Helicobacter-infected stomachs coincident with spasmolytic polypeptide-expressing metaplasia (SPEM), a precursor of gastric cancer. We aimed to characterize SLFN4+ cell identity and the role of Slfn4 in these cells.MethodsSingle-cell RNA sequencing was performed on immune cells sorted from PBMCs and stomachs prepared from uninfected and 6-month H. felis-infected mice. Knockdown of Slfn4 by siRNA or PDE5/6 inhibition by sildenafil were performed in vitro. Intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previously, Ding et al demonstrated that SLFN4+ myeloid-derived suppressor cells (MDSCs) could migrate to the stomach following Helicobacter pylori infection potentiating the development to gastric metaplasia [58]. Similarly, SLFN12L (which exhibits sequence similarity with Slfn4) has been shown to colocalize with MiR130b, a microRNA that was associated with SLFN4+ MDSCs that suppressed T cells and promoted Helicobacter-induced metaplasia [59].…”
Section: Schlafens and Immune Cellsmentioning
confidence: 99%
“…Previously, Ding et al demonstrated that SLFN4+ myeloid-derived suppressor cells (MDSCs) could migrate to the stomach following Helicobacter pylori infection potentiating the development to gastric metaplasia [58]. Similarly, SLFN12L (which exhibits sequence similarity with Slfn4) has been shown to colocalize with MiR130b, a microRNA that was associated with SLFN4+ MDSCs that suppressed T cells and promoted Helicobacter-induced metaplasia [59].…”
Section: Schlafens and Immune Cellsmentioning
confidence: 99%
“…Then, these cells differentiate and mature under the induction of factors such as IFN-α, express GLI1-dependent schlafen 4 and secrete interleukin (IL)-1β to activate the IL-6/phosphorylated signal transducer and activator of transcription (STAT)-3 pathway. The activation of SHH during Hp infection was closely related to the expression of programmed death-ligand 1 (PD-L1) ( 128 ), as well as the emergence of myeloid-derived suppressor cells (MDSCs), intestinal metaplasia and soluble polypeptide expression metaplasia ( 129 ).…”
Section: Tumor-promoting Inflammationmentioning
confidence: 99%